2003
DOI: 10.19173/irrodl.v4i1.129
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of Support in Online Interaction

Abstract: <P class=abstract>Peer-to-peer interaction using computer-mediated communication (CMC) would appear to be a promising source of timely and cost-effective student support, but little empirical evidence regarding actual participant support behaviour has been presented (Lee, 2000). This paper reports a study of the occurrence of 13 online strategies defined as &ldquo;supportive,&rdquo; according to the categorizations found in an instrument called the <I>Transcript Analysis Tool</I> (TAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
2
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 14 publications
3
30
2
7
Order By: Relevance
“…The lack of a formal structure to the blogging activity has shown that the students are able to take responsibility for their own learning and can use the new tool in a "deep" way without being instructed by the tutor. In contrast to other e-learning theories of online interaction (Salomon 2000;Fahy 2003), this research indicates that the quality of interaction does not have a progressive trajectory. Selfreflection (regarded as the most advanced skill in the learning process) may be enhanced by unstructured and accidental communication with others even at the very early stage of online interaction.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The lack of a formal structure to the blogging activity has shown that the students are able to take responsibility for their own learning and can use the new tool in a "deep" way without being instructed by the tutor. In contrast to other e-learning theories of online interaction (Salomon 2000;Fahy 2003), this research indicates that the quality of interaction does not have a progressive trajectory. Selfreflection (regarded as the most advanced skill in the learning process) may be enhanced by unstructured and accidental communication with others even at the very early stage of online interaction.…”
Section: Resultscontrasting
confidence: 99%
“…There were posts from the same students throughout the whole module whose style did not change and whose messages were purely descriptive with no self-reflection (eight per cent of the whole interaction traffic). From eight types of online interaction categories defined by Fahy (2003), those basic messages included "vertical questions" which seek correct answer from other participants. In my classification of knowledge accusation they were confined in stream 1 and 2.…”
Section: Researchmentioning
confidence: 99%
“…Ο συσχετισμός ανάμεσα στο δείκτη μάθησης και την ενεργό συμμετοχή στις κοινότητες, δείχνει ότι η μεγάλη και συστηματική συμμετοχή των φοιτητών στις κοινότητες, οδηγεί σε επίτευξη των μαθησιακών στόχων και στην υιοθέτηση της αντίληψης, ότι με αυτόν τον τρόπο μαθαίνουν πραγματικά (Sadera, Robertson, Song & Midon, 2009). Ένα ζήτημα που αναδεικνύεται εδώ είναι το ζήτημα της αλληλεπίδρασης μεταξύ των μελών της κοινότητας, το οποίο μελετήθηκε από τον Fahy (2003), όπου διαπιστώθηκε πως η αλληλεπίδραση (ειδικά η peer-to-peer αλληλεπίδραση) μπορεί να αποτελέσει μια πολύτιμη πηγή υποστήριξης και κάτω από ορισμένες συνθήκες θα μπορούσε να θεωρηθεί ακόμη και ως απαραίτητη για την πλήρη και επιτυχημένη (συνεργατική) μαθησιακή εμπειρία. Επειδή η ακριβής φύση αυτών των αλληλεπιδράσεων μπορεί να ποικίλει, διατυπώθηκαν αρχές που θα μπορούσαν να είναι χρήσιμες: (α) Ο διδάσκων μπορεί να μην είναι η κύρια πηγή υποστήριξης των φοιτητών.…”
Section: κοινότητες μάθησηςunclassified
“…In the case of e-learning for example, a useful framework is the Transcript Analysis Tool (TAT) (Fahy, 2003) as it offers:…”
Section: Content Analysismentioning
confidence: 99%
“…(Fahy, Crawford, Ally, 2001), while the advantages of TAT are (Fahy, 2003;Cook & Ralston, 2003;Fahy et al, 2001;Fahy, 2002): It reveals interaction patterns useful in assessing different communication styles and online behavioral preferences among participants; It regonizes the complexity of e-conferences and measures the intensity of interaction; It enables the processes occurring within the conferences to be noted and recorded; It probes beyond superficial systems data, which mask the actual patterns of discussion; It relates usefully to other work in the area; It discriminates among the types of sentences within the transcript; It reflects the importance of both social and task-related content and outcomes in transcript analysis research…”
Section: Purpose and Advantages Of The Tatmentioning
confidence: 99%